The Impact of Ethics on the Audit Quality of Firms in Sub-Sahara Africa - Mvunabandi, Jean Damascene; Maama, Haruna (International Journal of Economics and Financial Issues, 2023)
Sub-Saharan Africa (SSA) is a region characterised by unique challenges related to weak governance structures, inadequate regulatory frameworks, and limited resources. These challenges pose significant risks to audit quality, as they can compromise the independence, objectivity, and professional judgment of auditors. Moreover, the ethical values of the region can also have a significant impact on audit quality, as they shape the behaviour and attitudes of auditors and the firms they audit. The aim of this study was to investigate the impact of ethics on audit quality among firms in SSA. The study uses a sample of 323 firms from 12 sub-Saharan African countries, covering the period from 2012 to 2021. The research design is quantitative, employing a panel data approach and regression analysis. The econometric model used to estimate the impact of ethics on audit quality was based on variables such as audit quality, ethical values, tenure, audit size, auditor reputation, firm size, return on assets, ownership structure and board independence. The data was collected from the World Economic Forum, Bloomberg Database and other sources. Regression results demonstrated a negative and insignificant impact of ethical values on audit quality. However, the tenure of auditors had a positive impact on audit quality. The results of this study suggest the importance of promoting ethical behaboiur and strengthening ethial standards in auditing profession in SSA.